The Impact of Total Quality Management on Customer Satisfaction: A Case Study of PT Taspen (Persero) Nias Archipelago Branch - Nazara, Nefi Idaman Kasih; Marta Surya Dinata Mendrofa, Tri Hartati S. Hulu, Jeliswan Berkat Iman Jaya Gea, (Pascasarjana STIE Amkop Makassar, 2024)
This study aims to examine the impact of Total Quality Management (TQM) on customer satisfaction at PT. Taspen (Persero) Nias Islands Branch. TQM is an approach focused on enhancing organizational competitiveness through continuous improvement in product quality, services, people, processes, and the environment. The research uses a quantitative method, with 43 respondents consisting of employees and customers of PT. Taspen (Persero) Nias Islands Branch. Data collection was done through questionnaires, followed by validity and reliability tests, classical assumption tests (normality test), simple linear regression, and hypothesis testing (t-test, f-test, and coefficient of determination). The findings indicate that TQM influences customer satisfaction by 72%, while the remaining 28% is influenced by other factors not explored in this study. Keywords: Total Quality Management, Customer Satisfaction